Ellagic acid inhibits proinflammatory intermediary manufacture by suppressing NF-?B/Akt, VEGF and activating Nrf-2/Caspase-3 signaling pathways in rat testicular damage: a new way for testicular damage cure and in silico approach - Aslan, Abdullah; Gok, Ozlem; Beyaz, Seda; Uslu, Harun; Erman, Fazilet; Erman, Orhan; Baspinar, Serpil (Taylor & Francis Ltd, 2022)
Ellagic acid (EA) has protective effect on testicular damage and this natural compound decreases oxidative damage. The present study aims to examine the preventive effect of ellagic acid (EA) against carbon tetrachloride (CCl4)-induced testicular tissue damage in rats. In testicular tissue, tumor necrosis factor-alpha (TNF-alpha), Nuclear factor erythroid-2 related factor 2 (Nrf-2), B-cell lymphoma-2 (Bcl-2), vascular endothelial growth factor (VEGF), Nuclear factor-kappa B (NF-kappa B), cysteine aspartic proteases (caspase-3) and protein kinase B (Akt) synthesis levels were analyzed by western blot method, reactive oxygen species (ROS) was measured by malondialdehyde (MDA) levels, Glutathione (GSH) level and catalase (CAT) by spectrophotometer. As a result, in comparison with the CCl4 group, caspase-3 and Nrf-2 protein synthesis levels increased in EA + CCl4 group, however, VEGF, Bcl-2, NF-kappa B, TNF-alpha and Akt protein synthesis levels decreased, EA application raised GSH levels and CAT activity, reduced MDA levels. In this study, in silico tools were applied to confirm the activity of EA against the cancer with macromolecules such as the above mentioned transcription factors. EA, turned out to show significant activity similarly to some cocrystal ligands, particularly against cancer. These results points out that EA can be used as a testicular damage cure drug in future.
Keywords: Ellagic acid; NE-kappa B; Nrf-2; testicular damage; molecular docking